A Monetary Policy Rule for Jamaica - Sun, Yan. (Washington, D.C. : International Monetary Fund, 2005)
Since 1996, the Bank of Jamaica (BoJ) has sought to limit changes in the exchange rate for the Jamaican dollar in the context of its efforts to maintain low inflation. However, with a persistently high public sector deficit, real interest rates have remained generally high, which partly explains the slow pace of growth. This paper discusses an alternative monetary policy mix for achieving low variance for inflation and output through the prism of an empirical macroeconomic model. The simulation results suggest that a monetary policy mix that takes into account the impact of policy on both inflation and output achieves lower variance for inflation and output compared with the current policy mix, which tilts somewhat toward exchange rate stabilization. A case, therefore, can be made for the BoJ to move to a soft inflation targeting regime supported by fiscal consolidation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet